2018
DOI: 10.1080/21691401.2018.1426007
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastasis target redox-responsive micell for the treatment of lung cancer bone metastasis and anti-bone resorption

Abstract: In order to inhibit the growth of lung cancer bone metastasis and reduce the bone resorption at bone metastasis sites, a bone metastasis target micelle DOX@DBMs-ALN was prepared. The size and the zeta potential of DOX@DBNs-ALN were about 60 nm and -15 mV, respectively. DOX@DBMs-ALN exhibited high binding affinity with hydroxyapatite and released DOX in redox-responsive manner. DOX@DBMs-ALN was effectively up taken by A549 cells and delivered DOX to the nucleus of A549 cells, which resulted in strong cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Quantitative Evaluation. The maximum a posteriori Bayesian (MAPB) method [17], the sparse regularized Poisson denoising (SRPD) algorithm [18], and the wavelet packet transform (WPT) denoising algorithm [19] were introduced into the text, which was quantitatively compared with the OMAPB algorithm proposed in this study. Peak signal to noise ratio (PSNR) and Mean Structure Similarity (MSSIM) were used as evaluation indicators.…”
mentioning
confidence: 99%
“…Quantitative Evaluation. The maximum a posteriori Bayesian (MAPB) method [17], the sparse regularized Poisson denoising (SRPD) algorithm [18], and the wavelet packet transform (WPT) denoising algorithm [19] were introduced into the text, which was quantitatively compared with the OMAPB algorithm proposed in this study. Peak signal to noise ratio (PSNR) and Mean Structure Similarity (MSSIM) were used as evaluation indicators.…”
mentioning
confidence: 99%
“…The hyperglycemic conditions induce the accelerated formation and accumulation of AGEs, which directly inhibits osteoblasts and upregulates sclerostin in osteocytes. In addition, the high-glucose level increases the secretion levels of sclerostin in osteocytes and further inhibits osteoblasts by suppressing the Wnt/β-catenin pathway (Ye et al, 2018). In this study, type 2 diabetic mice showed significant inhibition of bone formation, and high glucose significantly inhibited the differentiation and migration of MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 53%
“…The micelles were prepared by dialysis method [ 38 ]. First, the DS-cad-DXM and DXM were dissolved into the DMSO and then slowly added into the deionized water with vigorous stirring.…”
Section: Methodsmentioning
confidence: 99%